2012
DOI: 10.1021/nl301230g
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Size Dependence of the Thermal Conductivity of Graphene Ribbons

Abstract: We investigated the thermal conductivity K of graphene ribbons and graphite slabs as the function of their lateral dimensions. Our theoretical model considered the anharmonic three-phonon processes to the second-order and included the angle-dependent phonon scattering from the ribbon edges. It was found that the long mean free path of the longwavelength acoustic phonons in graphene can lead to an unusual non-monotonic dependence of the thermal conductivity on the length L of a ribbon. The effect is pronounced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(211 citation statements)
references
References 52 publications
15
192
1
Order By: Relevance
“…An increase in the width of the wide region W w does not increase the unit cell any further, and thus, it does not affect the constriction resistance which is already formed. This was also observed by Nika et al [9] and Moore et al [25]. Sullivan et al using molecular dynamics in the case of Si nanowires in the presence of nano-constrictions, justified the irrelevance of large W w on the thermal conductance by explaining that the increase of the corrugation amplitude beyond a certain limit introduces atomic heat current separation between the corrugated ridges and the inner channel [23].…”
Section: The Effect Of the Narrow Regions' Widthsupporting
confidence: 56%
See 2 more Smart Citations
“…An increase in the width of the wide region W w does not increase the unit cell any further, and thus, it does not affect the constriction resistance which is already formed. This was also observed by Nika et al [9] and Moore et al [25]. Sullivan et al using molecular dynamics in the case of Si nanowires in the presence of nano-constrictions, justified the irrelevance of large W w on the thermal conductance by explaining that the increase of the corrugation amplitude beyond a certain limit introduces atomic heat current separation between the corrugated ridges and the inner channel [23].…”
Section: The Effect Of the Narrow Regions' Widthsupporting
confidence: 56%
“…Examples of these features include that: i) the thermal conductivity could deviate from Fourier's law [1][2][3][4][5], ii) a crossover is observed from ballistic into diffusive transport regimes [6,7], or from nanoto macro-scale behaviors [8,9], iii) the thermal conductivity could even increase under channel width confinement [10,11], iv) band mismatch under extreme confinement could result to phonon localization and 'effective transmission bandgaps' [12], v) heat transport could be below the Casimir or the amorphous limits, and many more [13,14]. Several interesting device concepts have also emerged recently in the area of phononics, which attempt to use heat to perform transistor action [15], create heat rectifiers [16], engineer the sound velocities and phonon dispersions, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies 9,23,[48][49][50] showed that the thermal conductivity of graphene increases logarithmically (~logL) with the size of sample, which is taken to fit MD results shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical investigations employed different models of the lattice vibrations, molecular dynamics simulations, density functional method and Boltzmann transport equation approach [13][14][19][20][21][22][23]. Recently the attention has been shifted to twisted few-layer graphene (T-FLG), which demonstrates intriguing electron [24][25][26][27] and phonon properties [28][29][30][31][32][33][34][35][36].…”
mentioning
confidence: 99%